Association of risk factors of GDM with outcome of GCT in obstetrical population - Sohail, Rubina; Bashir, Tahir; Javaid, Khalida; Zaman, Farrukh (Annals of King Edward Medical University, 2016)
Objective: To determine the association of risk factors of Gestational Diabetes Mellitus (GDM) to outcome of Glucose Challenge Test (GCT). Place and Duration of Study: From February 2000 to October 2000 at the antenatal clinic of Unit-II at Services Hospital. Subject and Methods: One thousand pregnant women attending antenatal clinic at 24-28 weeks of gestation at Services Hospital were included. Glucose challenge test was performed after a history with special reference to diabetic risk factors. Results: Risk factors were identified in 198 (19.8%); while there were no risk factors in 802 (80.2%) women. An oral glucose tolerance test (OGTT) was carried out in all glucose challenge test positive patients. Out of 198 women with risk factors, 50 women were glucose challenge test positive while 148 were screen negative. Out of 802 women without risk factors 54 were GCT positive while 748 were screen negative. The positive predictive value was 48% and the negative predictive value was 83% Out of ten gestational diabetic women, six (3%) belonged to the risk factor group While four (0.5%) were in the no risk factor group. Conclusion: pregnant women with positive risk factors for diabetes mellitus were found to have a six times greater chance of developing gestational diabetes as compared to those with no risk factors.